Preparation method of compound and application of compound in photocatalytic degradation of antibiotics
By preparing three-dimensional microporous cobalt compounds, the problem of difficult removal of antibiotic pollution in the environment is solved, and the efficient degradation and stability of ornizole under ultraviolet light is achieved. It is suitable for the treatment of various wastewater environments.
Patent Information
- Application Number
- CN202510054803.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-14
- Publication Date
- 2025-04-18
AI Technical Summary
The prior art is difficult to effectively remove antibiotic pollution in the environment, especially ornizole, and traditional treatment methods have problems of high cost and low efficiency.
Using a three-dimensional microporous cobalt compound preparation method, a mixture of organic ligands 2,5-bis(4'-pyridine)phenol, trichrylic acid and Co(CH3COO)2·4H2O is heated under specific conditions and controlled pH value to form a three-dimensional cobalt-based MOF with unique structure and high stability.
This compound exhibits significant antibiotic degradation efficiency under ultraviolet light, especially for ornizole, and remains stable in multiple cycles, making it a practical photocatalyst suitable for a variety of wastewater environments.
Smart Images

Figure CN119838638A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of compound preparation, and more specifically, to a method for preparing a compound and its application in photocatalytic degradation of antibiotics. Background Art
[0002] Antibiotics are widely used to treat various diseases. However, people's increasing dependence on antibiotics has led to major environmental challenges. Since most antibiotics have significant biological toxicity, once they enter the environment, their toxicity and high residual properties will take effect, and they will transform, disperse and enrich in various forms (i.e., migrate). They can enter the human body through the atmosphere, water, food, etc., accumulate in certain organs of the human body, cause poisoning, and endanger human health. Ornidazole (ODZ) is a member of the antibiotic drugs. Excessive use will not only cause drug resistance, but studies have also found that excessive use of ornidazole antibiotics can also cause certain damage to the body.
[0003] At present, treatment technologies such as adsorption, membrane separation and electrochemical degradation have been applied to the removal and treatment of antibiotic residues in the environment to eliminate and reduce the lasting effects of antibiotics on biological systems. Photocatalysis is considered to be the most promising method to solve environmental problems. Since the photocatalytic properties of TiO2 were discovered in 1972, in order to explore the application of photocatalysts, people have developed technologies for photocatalytic water decomposition and photocatalytic degradation of organic pollutants.
[0004] Metal-organic frameworks (MOFs) are a class of materials characterized by their different structures, and their applications in CO2 capture, photoluminescence, dye adsorption, magnetism, drug delivery, sensing and photocatalysis have attracted people's attention. In particular, metal-organic framework (MOFs) compounds with specific structures have been rapidly developed in new materials because these compounds can be post-modified in structure, and they play an important role in photocatalysis. Because MOFs catalytic materials have the characteristics of fast reaction, convenient application and low cost. Therefore, it is very necessary to develop MOFs-based photocatalytic materials to degrade antibiotics in the environment. Summary of the invention
[0005] In order to solve the above technical problems, the present invention provides a method for preparing a compound and its application in photocatalytic degradation of antibiotics.
[0006] A method for preparing a three-dimensional microporous cobalt compound comprises the following steps: S1: dissolving a mixture of organic ligand 2,5-di(4′-pyridine)phenol, trimesic acid and Co(CH3COO)2·4H2O in a container; S2: N,N′-dimethylacetamide added to the container; S3: Then add HNO3 aqueous solution and H2O dropwise, and measure the pH to be 6.5, at which point the solution is clear; S4: Seal the container, heat it to 107ºC and keep it warm for 5 days, then cool it down to room temperature at a rate of 5ºC / h. At this time, block crystals precipitate in the container; The obtained compound: {[NH2(CH3)2][Co5(BTC)3(OAC)2(DMA)2] n ·1.25DMA·2.25H2O}; The molecular formula of the compound is C 46 H 56.75 5N 4.25 O 27.5 .
[0007] The invention discloses an application of a three-dimensional microporous cobalt compound, which is applied in the photocatalytic degradation of antibiotics.
[0008] The beneficial effects of the present invention are as follows: the compound prepared by the present invention is a three-dimensional cobalt-based MOF with a unique structure and photocatalytic performance. Its skeleton structure and high stability make it a photocatalytic material, especially for the degradation of antibiotic pollutants in the environment. The material shows significant degradation efficiency under ultraviolet light, especially for ornidazole (ODZ), and remains stable in multiple cycles, making it a practical photocatalyst. The photocatalytic performance of the compound is affected by water quality and inorganic anions, indicating that it has potential application value in a variety of wastewater environments. BRIEF DESCRIPTION OF THE DRAWINGS
[0009] Figure 1 This is a screenshot of the crystal data sheet of compound 1 of the present invention; Figure 2 is a diagram of the coordination pattern of the cobalt atom in the compound 1 of the present invention; Figure 3 is a structural description diagram of compound 1 of the present invention; Figure 3 Middle: a: wheel-shaped structure formed by Co(II) ions; b: 2D network diagram; c: 3D structure diagram; d: topological diagram of compound 1.
[0010] Figure 4 is the thermogravimetric analysis diagram of compound 1 of the present invention; Figure 5 is an optical property diagram of compound 1 of the present invention; Figure 5 Middle: a UV-visible spectrum; b: optical band gap diagram of compound 1.
[0011] Figure 6 is the degradation diagram of the antibiotic by compound 1 of the present invention; Figure 6 Middle: Different concentrations of ODZ: a, 30ppm; b, 40ppm; c, 50ppm; d: C / C0 vs. time; e: Reaction kinetics; f: Comparison of different doses; Figure 7 This is the degradation diagram of the antibiotic by compound 1 of the present invention at different doses; a, 3 mg / L; b, 5 mg / L; c, 10 mg / L; d, 15 mg / L; e: C / C0 versus time; f: Comparison of different doses.
[0012] Figure 8 This is a graph showing the repeatability and stability of compound 1 of the present invention; Figure 8 Middle: a: Reusability diagram; b: PXRD of compound 1 after recycling; Fig. 9 is a graph showing the photocatalytic efficiency of compound 1 of the present invention in different aqueous media; Fig. 9 Middle: Degradation in the presence of (a) DI; (b) river water; (c) tap water; (d) C / C0 versus time plot; (e) reaction kinetics; (f) comparative degradation in different aqueous media.
[0013] Fig.10 is a graph of the photocatalytic efficiency of the compound 1 of the present invention in the presence of inorganic anions; Fig.10 In: (a) HCO3 − Degradation in the presence of; (B) CO3 2− ;(C)SO4 2− ; (d) C / C0 versus time plot; (e) reaction kinetics; (f) comparative degradation in the presence of inorganic ions. DETAILED DESCRIPTION
[0014] The subject matter described herein will now be discussed with reference to example embodiments. It should be understood that the discussion of these embodiments is only to enable those skilled in the art to better understand and implement the subject matter described herein, and the functions and arrangements of the elements discussed may be changed without departing from the scope of protection of the contents of this specification. Each example may omit, replace or add various processes or components as needed. In addition, the features described relative to some examples may also be combined in other examples. Example 1
[0015] In this embodiment, a method for preparing a three-dimensional microporous cobalt compound is proposed, comprising the following steps: S1: dissolving a mixture of organic ligand 2,5-di(4′-pyridine)phenol, trimesic acid and Co(CH3COO)2·4H2O in a container; S2: N,N′-dimethylacetamide added to the container; S3: Then add HNO3 aqueous solution and H2O dropwise, and measure the pH to be 6.5, at which point the solution is clear. ; S4: Seal the container, heat it to 107ºC and keep it warm for 5 days, then cool it down to room temperature at a rate of 5ºC / h. At this time, block crystals precipitate in the container; The obtained compound: {[NH2(CH3)2][Co5(BTC)3(OAC)2(DMA)2] n ·1.25DMA·2.25H2O}; The molecular formula of the compound is C 46 H 56.75 5N 4.25 O 27.5 . Example 2
[0016] In this embodiment, an application of the compound prepared in Example 1 is proposed, which is applied in the photocatalytic degradation of antibiotics. Example 3
[0017] In this example, a compound was prepared according to the method in Example 1. The specific process is as follows: A mixture of 24.8 mg of organic ligand 2,5-di(4′-pyridyl)phenol (DPP, 0.10 mmol), 21.0 mg of trimesic acid (H3BDC, 0.10 mmol) and 37.4 mg of Co(CH3COO)2·4H2O (0.15 mmol) was dissolved in a small glass vial, and 2.5 mL of N,N′-dimethylacetamide (DMA) was added to the small glass vial.
[0018] Then add 1.0ml of HNO3 aqueous solution and 2.5ml of H2O, and measure the pH to be 6.5, at which point the solution is clear. Heat the sealed vial to 107ºC and keep it warm for 5 days, then cool it to room temperature at a rate of 5ºC / h, at which point block crystals precipitate out of the vial; That is, the compound {[NH2(CH3)2][Co5(BTC)3(OAC)2(DMA)2] n ·1.25DMA·2.25H2O} (1), the yield is 65%, the molecular formula is C 46 H 56.75 5N 4.25 O 27.5 , Elemental analysis calculated value of compound 1 (%): C, 39.34; H, 4.04; N, 4.24. Experimental value: C, 39.78; H4.13; N4.31%. Infrared (cm -1 ):3441b,2939b,2800b,2479b,1624s,1431s,1367m,1110m,1004s,769s,716s,619b,448s (b=broad peak, m=medium peak, s=sharp peak). Example 4
[0019] This example is used to determine the structure of compound 1 in Example 3.
[0020] After the crystals were cleaned with DMA, the crystals with suitable quality and size were selected and placed on the Bruker-AXS SMART CCDX-single crystal instrument. The data of the two crystals were obtained by using the monochromatic purified Mo-K α The diffraction data of the two crystals were collected by scanning with λ = 0.071073 Å and ω = 0.3°. The diffraction data were restored by SAINT software and the absorption correction was performed by SADABS route. The crystal structure was solved by SHELXTL software using the direct method and (F 2 ) The coordinates of non-hydrogen atoms and hydrogen atoms, isotropic temperature factors and anisotropic temperature factors of compound 1 were refined by least squares method until convergence. The solution and refinement of compound 1 were completed using SHELXL-97 program package. The relevant crystallographic data of compound 1 are listed in the attached Figure 1 Table 1 in .
[0021] Structural description of compound 1.
[0022] A three-dimensional microporous cobalt compound 1 with an anionic skeleton was obtained under hydrothermal synthesis conditions, {[NH2(CH3)2][Co5(BTC)3(OAC)2(DMA)2] n ·1.25DMA·2.25H2O}.
[0023] Compound 1 is a monoclinic system, and the coordination mode of the central atom cobalt is as follows Figure 2As shown, the Co1 ion is coordinated with five oxygen atoms, one oxygen atom comes from the DMA molecule and the other four oxygen atoms come from four protonated trimesic acid (BTC), forming a distorted square pyramid geometry. The Co2 and Co3 ions are hexacoordinated, forming an octahedral geometry with Co-O bond distances in the range of 1.99-2.32 Å. The two oxygen atoms coordinated by the Co2 ion come from one carboxylate (OAC) ion and the other four oxygen atoms come from four BTC. The two oxygen atoms coordinated by the Co3 ion come from two OACs and the other four oxygen atoms come from four BTC ligands. In compound 1, each bridging trimesic acid ligand is fully deprotonated and coordinated with six Co(II) ions to form a cartwheel structure ( Figure 3 a). Carboxylate ion OAC has a μ4-η 2 :η 2 Through the six carboxyl oxygen atoms of the OAC anion, six CoO3 octahedra are connected to each other to form cobalt clusters, which are connected together by BTC bridges to form a two-dimensional layer diagram along the AC plane ( Figure 3 b). In addition, these two-dimensional parallel lines are bridged by BTC to assemble into a three-dimensional network structure ( Figure 3 c). The pore volume calculated by Platon program is 691.7Å 3 , accounting for 18.8% of the total volume of compound 1. There is [NH2(CH3)2] in compound 1 + Cation, [NH2(CH3)2] + The cation comes from the decomposition of DMA, so compound 1 has an anionic skeleton. The three-dimensional topology of compound 1 is a (3,5,6) network structure, such as Figure 3 d.
[0024] Thermogravimetric analysis of compound 1.
[0025] The thermal stability of compound 1 was evaluated by thermogravimetric analysis (TGA). Figure 4 The first weight loss of compound 1 occurred between 80℃ and 320℃, with a weight loss of 15.4%, which can be attributed to the loss of 2.25 water molecules and 1.25 DMA molecules (theoretical value: 14.0%). The framework of compound 1 is stable up to 350℃, and then the organic matter decomposes.
[0026] Optical properties of compound 1 The optical properties of compound 1 were investigated by UV-visible spectroscopy to understand its interaction with light and to evaluate its potential applications. Figure 5As shown in Figure a, the UV-visible absorption spectrum of compound 1 shows obvious absorption peaks at 210 nm and 301 nm, which is attributed to the ligand-metal charge transfer (LMCT) process. In LMCT, electrons jump from ligand orbitals to metal orbitals, demonstrating the electronic interaction within the material and highlighting its ability to absorb light of specific wavelengths.
[0027] By analyzing the UV-visible absorption data using the Tauc formula, the optical band gap energy of compound 1 was calculated to be 1.6 eV, as shown in Figure 5 b. This relatively low band gap value confirms the semiconductor nature of compound 1, indicating that compound 1 can conduct electricity under certain conditions. The semiconductor properties of compound 1 make it have great application prospects in electronics, optoelectronics and materials science, especially in sensors, photovoltaic devices and light-emitting diodes (LEDs). Example 5
[0028] This example is used to study the degradation of antibiotics by compound 1.
[0029] The photocatalytic degradation properties of compound 1 towards antibiotics tinidazole (TDZ), dimethoxonidazole (DTZ), ornidazole (ODZ), ciprofloxacin (CIP) and β-lactamase (BCL) were studied. Figure 6 As shown. Under dark conditions, compound 1 showed negligible degradation of antibiotics. However, under UV light irradiation, 10 mg of compound 1 showed significant degradation of 40 ppm solutions of various antibiotics within 60 min. The degradation efficiencies of TDZ, DTZ, ODZ, CIP, and BCL were 51.9%, 56.87%, 64.52%, 35.44%, and 48.68%, respectively. Among them, compound 1 was particularly effective in degrading ODZ, which may be due to its semiconductor properties promoting efficient electron-hole pair generation under UV irradiation.
[0030] In order to optimize the degradation performance of compound 1 on ODZ, the experiment explored the effects of ODZ concentration and the dosage of compound 1 on the degradation efficiency. First, different concentrations of ODZ ( Figure 6 ). At 30 ppm, the degradation efficiency was 54.85%, while at 40 ppm, the degradation efficiency increased to a maximum of 64.52%. However, at higher concentrations (such as 50 ppm), the degradation efficiency slightly decreased to 63.20%, which was due to the fact that the excessive concentration covered the photocatalyst surface and reduced the light interaction. Secondly, changing the dosage of compound 1 ( Figure 7). At a low dosage of 3 mg / L, the degradation rate reached 81.62%, and at a dosage of 5 mg / L, the degradation rate increased to 83.69%. At a dosage of 10 mg / L, the degradation efficiency dropped to 64.52%, and at a dosage of 15 mg / L, the degradation efficiency dropped to 26.82%. This reduction at higher dosages is attributed to the excess photocatalyst particles blocking the penetration of light, reducing the number of photons that interact with the ODZ molecules.
[0031] The results showed that the optimal photocatalytic degradation conditions for compound 1 were 5 mg / L catalyst dosage, 40 ppm ODZ concentration, and 83.69% degradation. These findings highlight the potential of compound 1 as an effective photocatalyst for treating antibiotic pollutants under optimized conditions.
[0032] Reproducibility and stability of photocatalysts.
[0033] The repeatability and stability of photocatalysts are important factors in evaluating their practicality. To evaluate these properties, a series of cycling experiments were performed using compound 1 for the photodegradation of ODZ. After each cycle, compound 1 was separated from the reaction mixture by filtration and washed clean, dried at room temperature, and then reused. The results showed that compound 1 maintained its photocatalytic efficiency over consecutive cycles without any significant decrease in performance, which indicates that compound 1 has repeatability, such as Figure 8 As shown in a.
[0034] To further demonstrate the stability of compound 1 during the recycling process, powder XRD analysis was performed before and after the use cycle. PXRD remained unchanged ( Figure 8 b), indicating that the structure of compound 1 remains unchanged throughout repeated photocatalytic cycles. This stability ensures that the active sites in compound 1 remain fully functional even after long-term use. Compound 1 has good repeatability and stability as a photocatalyst material.
[0035] Photocatalytic efficiency of compound 1 in different aqueous media.
[0036] The photocatalytic efficiency of compound 1 was evaluated in three water sources: tap water, deionized water, and river water to assess its performance under different environmental conditions. The experiments were carried out under optimized conditions ( Fig. 9 ).
[0037] Tap water: In tap water, compound 1 showed a high degradation efficiency of 82.53% for ODZ. Controlling the composition of tap water, the content of organic and inorganic impurities was relatively low, allowing compound 1 to operate effectively. This result proves that the photocatalyst is suitable for semi-pure water environment with minimal interference.
[0038] River Water: The degradation efficiency of ODZ in river water was slightly lower at 70.71%. This reduction in efficiency was attributed to the various organic and inorganic substances naturally present in river water. These substances can adsorb onto the surface of compound 1, reduce the available active sites for ODZ degradation, and compete with ODZ to interact with the reactive oxygen species generated during the photocatalytic process. Despite this, the photocatalytic performance of compound 1 in river water was still strong, illustrating the potential of compound 1 in real-world environmental remediation. Deionized Water (DI): In deionized water, compound 1 showed the highest degradation efficiency of 83.69%. The absence of impurities and competing species in deionized water allowed for the most efficient photocatalytic activity. The purity of the medium ensured the best interaction between the ODZ molecules and the active species generated by compound 1, leading to excellent degradation performance.
[0039] The experimental results show that compound 1 is very effective in degrading ODZ in different aqueous media. The excellent efficiency in deionized water and tap water indicates the great potential of compound 1 in controlled water treatment applications, while its effectiveness in river water highlights its ability in broader environmental remediation. These findings illustrate the reliability of compound 1 as a photocatalyst under different water conditions.
[0040] Photocatalytic efficiency of compound 1 in the presence of inorganic anions.
[0041] Among common inorganic anions, including sulfate ion (SO4 2− ), bicarbonate ion (HCO3 − ) and carbonate ions (CO3 2− ) was used to evaluate the photocatalytic degradation of ornidazole (ODZ) by compound 1. Fig.10 ). These anions are commonly found in natural and industrial water sources and can affect the photocatalytic activity by interacting with reactive oxygen species (ROS) or the photocatalyst surface.
[0042] In the absence of anions: In the absence of any anion, the degradation rate of ODZ by compound 1 was as high as 83.69%. This result indicates the optimal performance of compound 1 under ideal conditions, in which there are no competitive interactions that affect the photocatalytic process.
[0043] In SO4 2− In the presence of: Sulfate ion (SO4 2−) slightly decreased the degradation efficiency to 78.99%. Sulfate ions may partially interfere with the active sites on the surface of compound 1 or consume some of the ROS generated during the photocatalytic process, thereby reducing the availability of ROS for ODZ degradation. Nevertheless, the efficiency is still relatively high, indicating the stability of compound 1 in the presence of sulfate.
[0044] In HCO3 − In the presence of: When bicarbonate ions (HCO3 − ), the degradation efficiency further decreased to 73.74%. Bicarbonate ions can act as a scavenger of free radicals, especially reacting with hydroxyl radicals (•OH), reducing their concentration and effectiveness in degrading ODZ. This explains the more significant effect on the photocatalytic efficiency compared with sulfate ions.
[0045] In CO3 2− In the presence of: Interestingly, carbonate ions (CO3 2− ) resulted in an increase in the degradation efficiency to 94.16%. Carbonate ions can sometimes stabilize ROS or enhance the catalytic surface properties, thereby improving the overall photocatalytic performance. This positive effect demonstrates that CO3 2− The unique interaction between it and compound 1 enhances the degradation efficiency of ODZ.
[0046] In the presence of common anions, the photocatalytic activity of compound 1 remained high, with only minor changes due to their interactions with ROS or the catalyst surface. 2− ) and bicarbonate (HCO3 − ) slightly reduces the degradation efficiency by competing with ROS, while carbonate (CO3 2− ) enhanced the degradation performance, resulting in the highest observed degradation efficiency of 94.16%. These findings demonstrate the adaptability and potential of compound 1 for use in wastewater environments containing various inorganic ions.
[0047] The above describes an embodiment of the present embodiment, but the present embodiment is not limited to the above-mentioned specific implementation methods. The above-mentioned specific implementation methods are merely illustrative and not restrictive. Under the guidance of the present embodiment, ordinary technicians in this field can also make many forms, all of which are protected by the present embodiment.
Claims
1. A method for preparing a compound, characterized in that: The steps include: S1: dissolving a mixture of organic ligand 2,5-di(4′-pyridine)phenol, trimesic acid and Co(CH3COO)2·4H2O in a container; S2: N,N′-dimethylacetamide added to the container; S3: Then add HNO3 aqueous solution and H2O dropwise, and measure the pH to be 6.5, at which point the solution is clear; S4: Seal the container, heat it to 107°C and keep it warm for 5 days, then cool it down to room temperature at a rate of 5°C / h. At this time, block crystals precipitate out of the container; The obtained compound: {[NH2(CH3)2][Co5(BTC)3(OAC)2(DMA)2] n ·1.25DMA·2.25H2O}; The molecular formula of the compound is C 46 H 56.75 5N 4.25 O 27.5 .
2. Use of a compound, characterized in that: Application in photocatalytic degradation of antibiotics.